Overlaping Fungsi Baitul Mal dan Kantor Urusan Agama sebagai Lembaga Pengelola Wakaf (Kritik terhadap Peran Baitul Mal sebagai Lembaga Pengelola Wakaf di Aceh) - Hidayatina MA; Ali Muhayatsyah (State Institute of Islamic Studies (IAIN) Salatiga, 2019)
Although Aceh Qanun Number 10 of 2007 mandated Baitul Mal as a waqf manager, there was overlapping both in regulation and implementation between the Baitul Mal, KUA and BWI. The purpose of this study is to examine the obstacles and opportunities of Baitul Mal as waqf management institution in developing waqf management in Aceh. The method used is in the form of field research with the normative juridical approach. The results of this study are: a) The obstacles of Baitul Mal as Waqf Managers are: (1) the regulation of waqf management function in Baitul mal does not yet have rules for the management of waqf property; (2) the KUA function is not optimal in managing waqf because it is still limited to administrative issues and the law has not been fully implemented; and (3t The emergence of BWI to take over management of waqf has resulted in many rules and more overlapping of management of waqf; b) Baitul Mal is very likely to manage waqf because of regulation. Even though there are other institutions such as KUA and BWI that also have regulations, autonomously, the Aceh Government still has a strategic place to manage waqf.